Urine brilliance: urine TB LAM's role in challenging AIDS cases from LMIC's perspective - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Hussin, Fara Rahidah; Periyasamy, Petrick (Elsevier Ltd, 2024)
The identification of reliable markers for active tuberculosis (TB) diagnosis is pivotal, especially in challenging scenarios, particularly in low- and middle-income countries (LMICs), where co-infections, notably among individuals with AIDS, pose significant diagnostic challenges. Lipoarabinomannan (LAM), an immunogenic virulence factor released from metabolically active or degrading mycobacteria, presents a promising avenue for overcoming these hurdles. In this study, we present a case series that underscores the intricacies of TB diagnosis, specifically focusing on individuals co-infected with AIDS in LMICs.